2001
DOI: 10.1006/mthe.2001.0274
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Injection of Recombinant Adeno-associated Virus Improves Cognitive Function in a Murine Model of Mucopolysaccharidosis Type VII

Abstract: Mucopolysaccharidosis type VII (MPS VII) is a lysosomal storage disease caused by the lack of beta-glucuronidase (GUSB) activity. GUSB deficiency leads to the progressive accumulation of undegraded glycosaminoglycans (GAGs) in cells of most tissues, including the brain, and is associated with mental retardation. Reduction of lysosomal storage in the central nervous system and prevention of cognitive dysfunction may require intracranial delivery of a therapeutic agent during the newborn period that provides a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 40 publications
2
66
0
Order By: Relevance
“…35,36 In the present study, we utilized the CMV-enhanced chicken b-actin promoter with the b-actin/rabbit b-globin hybrid intron, a promoter/intron combination that has been shown to successfully drive the expression of an AAV vector-mediated transfer of a gene in the brain for 41 year. 16 The combination of the long-term expressing vector AAV2 and a strong nonviral promoter led to robust TPP-I expression in the brain of rats for 418 months and for at least 3 months (the longest time period examined to date) in the brains of non-human primates in the present study. Owing to resources needed, there is limited data on long-term transgene expression in nonhuman primates beyond 90 days as described here, although one report shows persistent expression up to 134 days.…”
Section: Aav-mediated Cns Transfer Of Cln2 D Sondhi Et Almentioning
confidence: 51%
See 1 more Smart Citation
“…35,36 In the present study, we utilized the CMV-enhanced chicken b-actin promoter with the b-actin/rabbit b-globin hybrid intron, a promoter/intron combination that has been shown to successfully drive the expression of an AAV vector-mediated transfer of a gene in the brain for 41 year. 16 The combination of the long-term expressing vector AAV2 and a strong nonviral promoter led to robust TPP-I expression in the brain of rats for 418 months and for at least 3 months (the longest time period examined to date) in the brains of non-human primates in the present study. Owing to resources needed, there is limited data on long-term transgene expression in nonhuman primates beyond 90 days as described here, although one report shows persistent expression up to 134 days.…”
Section: Aav-mediated Cns Transfer Of Cln2 D Sondhi Et Almentioning
confidence: 51%
“…[11][12][13][14][15][16][17] Second, mucopolysaccharidosis VII, a related lysosomal storage disease, has been successfully reversed in a knockout mouse model by recombinant AAV2-mediated intracranial gene transfer. 16,[18][19][20] Third, a significant fraction of newly synthesized TPP-I protein is secreted as pro-TPP-I, a 563 amino-acid inactive form which can crosscorrect nearby nontransduced cells through mannose 6-phosphate receptor-mediated uptake and subsequent activation in lysosomes to the 367 amino-acid mature form. 21,22 This cross-correction between transduced cells and neighboring cells suggests that it will not be necessary to transfer the normal CLN2 cDNA to all the cells in the CNS, thus extending the effective range of gene transfer to broader regions of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse brain, gene transfer using three recombinant AAV serotypes, AAV2, AAV4, and AAV5, with a variety of promoters and genes has been performed. [3][4][5]7,8,17,[31][32][33][34] All but two studies examined AAV2-mediated transduction alone. 17,35 A direct comparison of intracerebral injection in adult mice of AAV2, AAV4, and AAV5, each containing the Rous sarcoma virus (RSV) long-terminal repeat promoter and the lacZ gene, found that AAV2 and AAV5 could transduce cells in the striatum, but that AAV5 resulted in greater numbers of positive cells at longer time points, whereas, AAV4 resulted in almost exclusive transduction of ependymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many invasive strategies have been used or proposed for circumventing the blood-brain barrier, including intraparenchymal injections of therapeutic proteins, intraparenchymal gene therapy, chemical or physical agents to open the blood-brain barrier (such as mannitol), and hematopoietic stem cell transplantation [1][2][3][4][5][6][7][8][9]. Treatment via the cerebrospinal fluid has not been successful in the past due to the inability of the proteins to traverse the ependymal layer and diffuse through brain tissue, even though this route would be clinically easier for application to patients.…”
Section: Introductionmentioning
confidence: 99%